Characterizing tertiary lymphoid structures associated single-cell atlas in breast cancer patients - Xiaokai Fan; Daqin Feng; Donggui Wei; Anqi Li; Fangyi Wei; Shufang Deng; Muling Shen; Congzhi Qin; Yongjia Yu; Lun Liang (Cancer Cell International)
Abstract The tertiary lymphoid structure (TLS) is recognized as a potential prognosis factor for breast cancer and is strongly associated with response to immunotherapy. Inducing TLS neogenesis can enhance the immunogenicity of tumors and improve the efficacy of immunotherapy. However, our understanding of TLS associated region at the single-cell level remains limited. Therefore, we employed high-resolution techniques, including single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics (ST), and a TLS-specific signature to investigate TLS associated regions in breast cancer. We identified eighteen cell types within the TLS associated regions and calculated differential expression genes by comparing TLS associated regions with other areas. Notably, macrophages in the TLS associated regions exhibit lineage transformation, shifting from facilitators of immune activation to supporters of tumor cell growth. In terms of cell–cell communication within the TLS associated regions, KRT86+ CD8+ T cells, HISTIH4C+ cycling CD8+ T cells, IFNG+ CD8+ T cells, and IGKV3-20+ B cells demonstrate strong interactions with other cells. Additionally, we found that APOD+ fibroblast and CCL21+ fibroblast primarily recruit T and B cells through the CXCL12-CXCR4 ligand-receptor signaling pathway. We also validate these findings in four independent breast cancer datasets, which include one cell-level resolution dataset from the 10 × Xenium platform and three spot-level datasets from the 10 × Visium platform.